Magnetic resonance imaging arterial spin labeling hypoperfusion with diffusion-weighted image hyperintensity is useful for diagnostic imaging of Creutzfeldt–Jakob disease - Kitazaki, Yuki; Ikawa, Masamichi; Hamano, Tadanori; Sasaki, Hirohito; Yamaguchi, Tomohisa; Enomoto, Soichi; Shirafuji, Norimichi; Hayashi, Kouji; Yamamura, Osamu; Tsujikawa, Tetsuya; Okazawa, Hidehiko; Kimura, Hirohiko; et al. (Frontiers in Neurology, 2023)
Background and objectives Magnetic resonance imaging with arterial spin labeling (ASL) perfusion imaging is a noninvasive method for quantifying cerebral blood flow (CBF). We aimed to evaluate the clinical utility of ASL perfusion imaging to aid in the diagnosis of Creutzfeldt–Jakob disease (CJD). Methods This retrospective study enrolled 10 clinically diagnosed with probable sporadic CJD (sCJD) based on the National CJD Research & Surveillance Unit and EuroCJD criteria and 18 healthy controls (HCs). Diffusion-weighted images (DWIs), CBF images obtained from ASL, N-isopropyl-(123I)-p-iodoamphetamine (123IMP)-single-photon emission computed tomography (SPECT) images, and 18F-fluorodeoxyglucose (18FDG)-positron emission tomography (PET) images were analyzed. First, the cortical values obtained using volume-of-interest (VOI) analysis were normalized using the global mean in each modality. The cortical regions were classified into DWI-High (≥ +1 SD) and DWI-Normal (< +1 SD) regions according to the DWI-intensity values. The normalized cortical values were compared between the two regions for each modality. Second, each modality value was defined as ASL hypoperfusion (< −1 SD), SPECT hypoperfusion (< −1 SD), and PET low accumulation (< −1 SD). The overall agreement rate of DWIs with ASL-CBF, SPECT, and PET was calculated. Third, regression analyses between the normalized ASL-CBF values and normalized SPECT or PET values derived from the VOIs were performed using a scatter plot. Results The mean values of ASL-CBF (N = 10), 123IMP-SPECT (N = 8), and 18FDG-PET (N = 3) in DWI-High regions were significantly lower than those in the DWI-Normal regions (p < 0.001 for all); however, HCs (N = 18) showed no significant differences in ASL-CBF between the two regions. The overall agreement rate of DWI (high or normal) with ASL-CBF (hypoperfusion or normal) (81.8%) was similar to that of SPECT (85.2%) and PET (78.5%) in CJD. The regression analysis showed that the normalized ASL-CBF values significantly correlated with the normalized SPECT (r = 0.44, p < 0.001) and PET values (r = 0.46, p < 0.001) in CJD. Discussion Patients with CJD showed ASL hypoperfusion in lesions with DWI hyperintensity, suggesting that ASL-CBF could be beneficial for the diagnostic aid of CJD.